(untitled) (Pedagogy of Higher and Secondary Education, 2010)
The article deals with the concepts: personality, personality development, personality formation, socialization through cognitive interest and cognitive activity in training activities, as well as the influence of cognitive activity as a factor in the socialization of the individual students.